Actor-Network Theory and Sentiment Analysis on Regional Development Issues and Politics in Social Media - Yerik Afrianto Singgalen (Jurnal Komunikasi, 2021)
During the Covid-19 pandemic, North Halmahera Regency's political activity became intense in virtual spaces, especially on the Facebook group Quovadis North Halmahera. The things discussed in the virtual space have an impact on the community in the real world. Hate Speech and provocative issues generate negative responses in the real world, marked by conflicts in several social spaces.This article aims to discuss regional development issues and politics in social media based on sentiment analysis and actor-network theory. This article also identifies the vulnerability aspect by mapping and classifying netizen's argument in the virtual space to various regional development issues based on economic, social, cultural, political, tourism, and environmental aspects. This research uses qualitative methods. The process of collecting data uses in-depth interview techniques, observation, and document study. Data processing uses triangulation techniques. Also, research instruments used are QGIS 2.18.4 and Nvivo 12 Plus applications for mapping research sites and mapping development issues in virtual space, namely Quo Vadis Halmahera Utara Facebook group. This study indicates that social capital (Norm, Trust, Network) becomes an aspect of vulnerability based on mapping and content analysis in virtual space according to netizens' response to development issues in the North Halmahera Regency. Furthermore, the contents containing hate speech elements, invalid information (hoax), sarcasm, bullying, and privacy attacks are the potential actors to cause social capital degradation based on the Actor-Network-Theory. Selama Pandemi Covid-19, kondisi perpolitikan di Kabupaten Halmahera Utara menjadi intensif di ruang virtual, khususnya grup facebook QuoVadis Halmahera Utara. Pelbagai isu pembangunan dan politik di ruang virtual tersebut berdampak terhadap kondisi sosial masyarakat di kehidupan sehari-hari. Ujaran kebencian, isu profokatif hingga sentimen negatif memantik konflik di ruang sosial. Artikel ini bertujuan untuk mendiskusikan masalah pembangunan dan politik di media sosial berdasarkan analisis sentimen dan teori jejaring aktor. Artikel ini juga mengidentifikasi aspek kerentanan, dengan memetakan dan mengklasifikasikan argumen netizen di ruang virtual, menanggapi pelbagai persoalan sosial, budaya, politik, pariwisata dan lingkungan. Penelitian ini menggunakan metode kualitatif. Proses pengolahan data menggunakan teknik wawancara mendalam, observasi dan studi dokumen. Proses pengolahan data menggunakan trianggulasi. Instrumen penelitian yang digunakan ialah QGIS 2.18.4  untuk pemetaan lokasi atau wilayah penelitian dan Nvivo 12 Plus untuk pemetaan isu pembangunan dan politik yang didiskusikan dalam grup facebook Quovadis Halmahera Utara.  Hasil penelitian ini menunjukkan bahwa modal sosial (norma, kepercayaan, jejaring) menjadi aspek kerentanan. Selain itu, konten yang teridentifikasi dari hasil analisis sentimen ialah ujaran kebencian, informasi yang tidak valid, sarkasme, perundungan dan penyerangan privasi, sebagai penyebab degradasi modal sosial berdasarkan teori jejaring aktor.